Understanding and forecasting dispersal of non-indigenous marine decapods (Crustacea: Decapoda) in East European and North Asian waters. (27th March 2017) - Spiridonov, Vassily A.; Zalota, Anna K.
Abstract : A survey of publications and collections databases reveals a pattern of non-indigenous decapods distribution in the 13 seas around Russia and adjacent countries. No alien species were reported from Russian territorial waters and exclusive economic zone in the Japan, Okhotsk, west Bering and most of the Siberian shelf Seas. From the seas and their basins in East Europe, 13 alien species have been recorded, with seven of these yet to become established. Established or commonly occurring species can be categorized as: 'global invaders' (Chinese mitten crab, Eriocheir sinensis in the White, Baltic, Black, Azov and Caspian Seas; and Harris mud crab, Rhithropanopeus harrisii in all mentioned seas, except the White Sea); 'regional aliens' ( Palaemon adspersus and P. elegans in the Caspian Sea and the latter species in the Baltic); and 'Arctic invaders' (Kamchatka king crab Paralithodes camtschaticus and snow crab Chionoecetes opilio ). Eriocheir sinensis is the most widely occurring alien decapod species, but there are no indications of an established population in East Europe. For this and other mentioned crab species, invasion history, distribution and important biological data are reviewed. In the seas where few or no native crab species have been present, Harris mud crab (in the Azov and Caspian Seas), Kamchatka crab (in the Barents Sea) and snow crab (in the Barents and Kara Seas) have shown rapid establishment (within two decades) of an invasive population throughout an entire basis or its significant part.